Marketing Strategy through Spiritual Tourism : A Case Study of the Borobudur Vesak Lantern Festival - Wijayanto, Rudi; Aisyianita, Revi Agustin; Kusumawati, Fitri Dwi; Winda, Inda Citra (Lasigo Akademia Indonesia, 2025)
The Borobudur Vesak Lantern Festival is an annual event that serves as one of the main highlights in the series of Buddhist religious celebrations in Indonesia, held at Borobudur Temple. This study is of particular interest because the religious procession is not only attended by Buddhist adherents but also open to tourists from diverse religious backgrounds who wish to participate in the event. This research employs a qualitative method with a case study approach, in which data were collected through observation, interviews, and literature review. The primary objective of this study is to examine how marketing strategies are implemented within the context of an international-scale religious event. The findings reveal that the Vesak Lantern Festival at Borobudur has successfully transformed from a purely religious ceremony into a major tourism attraction. This success is supported by marketing strategies encompassing market segmentation, positioning, stakeholder collaboration, marketing mix, and effective timing strategies that collectively enhance tourist attraction. The impact is evident in the increase in visitor numbers, the growth of the local economy, and the strengthening of Borobudur’s image as a world-class spiritual tourism destination. This study contributes to a deeper understanding of how marketing principles can be aligned with spiritual values and used as a foundation for developing more effective marketing strategies that respect religious and cultural values. Future research may explore the extent to which the implementation of the Vesak Lantern Festival affects environmental sustainability within the Borobudur World Heritage Site and develop a green event management model to maintain a balance between tourism activities and environmental preservation.